Elementos de retórica na obra de Nietzsche - Rogerio Antonio Lopes (1999)
The present dissertation aims to describe the recurrence of the problem of rhetoric in Nietzsche's work. At first we concentrate in the theoretical treatment of the question by the author. The second part consists of an analysis and an articulation of elements found in Nietzsche's speech practice that allow a description in rhetorical terms (domain of style, discovering procedures, argumentative strategy and form of presentation).